2020
DOI: 10.3390/nano10081431
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Linezolid Combination as Potential New Anti-Tuberculosis Treatment

Abstract: Global pandemic management represents a serious issue for health systems. In some cases, repurposing of existing medications might help find compounds that have the unexpected potential to combat microorganisms. In the same way, changing cell–drug interaction by nanotechnology could represent an innovative strategy to fight infectious diseases. Tuberculosis (TB) remains one of the most alarming worldwide infectious diseases and there is an urgent need for new drugs and treatments, particularly for the emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…They also had used GO-PEG as a carrier for a specific antibiotic and confirmed the effectiveness of this carrier for improving the antibacterial activity of Tetracycline [ 62 ] (the same as the current study). Other studies have been conducted in this field that confirmed similar observations [ 66 , 67 , 68 ].…”
Section: Resultssupporting
confidence: 82%
“…They also had used GO-PEG as a carrier for a specific antibiotic and confirmed the effectiveness of this carrier for improving the antibacterial activity of Tetracycline [ 62 ] (the same as the current study). Other studies have been conducted in this field that confirmed similar observations [ 66 , 67 , 68 ].…”
Section: Resultssupporting
confidence: 82%
“…Graphene-oxide (GO) has a unique degree of in vivo specificity, biodegradability, low cellular toxicity, and enormous drug loading capacity ( McCallion et al, 2016 ). When administered in vivo , GO preferentially accumulates in lung cells ( De Maio et al, 2020 ) and inhibits the growth of Mycobacterium tuberculosis (Mtb), which is the prime microbial agent of tuberculosis infection ( Maio et al, 2019 ).…”
Section: Nabtsmentioning
confidence: 99%
“…GO has been successfully coupled with Linezolid to treat Mycobacterium tuberculosis ( De Maio et al, 2020 ), also known as multi-drug-resistant TB or extensively drug-resistant TB (XDR-TB). Metronidazole could be combined with GO and biomimetic PLGA or membrane-bound NPs to treat Clostridiodes (clostridium) difficile infections.…”
Section: Future Research Perspectivesmentioning
confidence: 99%
“…Moreover, GO modification with organic compounds that possess the antimicrobial activity and biocompatibility have been intensively studied very recently, e.g., chitosan (CS) [92,[101][102][103], curcumin [104,105], antimicrobial agents (isoniazid (INH), amikacin (AMK) and linezolid (LZD), lincomycin hydrochloride (LMH), chloramphenicol (CPC) and gentamycin sulfate (GMS) [106,107]) and dyes [108]. Chitosan exhibits high biocompatibility, biodegradability and antibacterial properties [109].…”
Section: Antimicrobial Properties Of Graphene-based Composite Photocatalystsmentioning
confidence: 99%